2011
DOI: 10.1186/1746-1596-6-s1-s20
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a remote quantitative image analysis in the whole slide images

Abstract: The rationale for choosing a remote quantitative method supporting a diagnostic decision requires some empirical studies and knowledge on scenarios including valid telepathology standards. The tumours of the central nervous system [CNS] are graded on the base of the morphological features and the Ki-67 labelling Index [Ki-67 LI]. Various methods have been applied for Ki-67 LI estimation. Recently we have introduced the Computerized Analysis of Medical Images [CAMI] software for an automated Ki-67 LI counting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…These programs are associated with an increasing number of publications that indicate quantitative morphometry is the equivalent of microscopic evaluation by conventional optical microscopy (Bernardo et al 2009;Lloyd et al 2011;Rojo, Bueno, and Slodkowska 2009;Słodkowska et al 2011).…”
Section: Quantitative Assessment Of Morphologic Changesmentioning
confidence: 99%
“…These programs are associated with an increasing number of publications that indicate quantitative morphometry is the equivalent of microscopic evaluation by conventional optical microscopy (Bernardo et al 2009;Lloyd et al 2011;Rojo, Bueno, and Slodkowska 2009;Słodkowska et al 2011).…”
Section: Quantitative Assessment Of Morphologic Changesmentioning
confidence: 99%
“…The first was a Polish study (n = 28) that examined the accuracy of a remote quantitative image analysis of tumors of the central nervous system using WSI. 87 The study assessed the accuracy and reliability of remote assessment of morphological features and the Ki-67 LI labeling index (an expression of nuclear antigen or cell proliferation) with computerized analysis of medical images (CAMI). The authors concluded that the results demonstrated that ''.the remote automated Ki-67 LI analysis performed with the CAMI algorithm on the whole slide images of meningiomas and oligodendrogliomas could be successfully used as an alternative method to manual reading as well as to digital images quantitation with CAMI software.''…”
Section: Telepathology Evidence: Feasibility and Acceptancementioning
confidence: 99%
“…Several studies have published comparisons between semiquantitative scoring systems and digital analysis techniques for immunohistochemical staining . The accuracy of digital techniques including Aperio computer‐assisted analysis of immunohistochemical staining techniques has been assessed and validated in multiple tissue types including brain, breast and kidney . In published literature, Aperio PPCA is comparable with the pathologist's scoring and could add benefits of automated and reproducible measurement .…”
Section: Discussionmentioning
confidence: 99%